학생조종사의 수동조작 기량과 상황인식 역량에 따른 시선 움직임 연구 - 권문진; 이장룡; Moonjin Kwon; Jang Ryong Lee (한국항공운항학회지, 2024)
This study analyzed the characteristics and differences in eye movements based on the manual control abilities and situation awareness of student pilots. The results revealed a strong correlation between situation awareness and flight performance, with level 2 (Comprehension) of situation awareness particularly reflecting overall situation awareness ability. This finding suggests that the capacity to not only perceive information but also to understand and interpret its significance is crucial in aviation. Eye-tracking analysis showed that student pilots with more advanced flight skills process speed information more efficiently and demonstrate higher situation awareness through active saccades between instruments. This suggests the importance of efficient visual attention distribution and visual scanning patterns. It implies that the ability to quickly and efficiently gather and process necessary information, rather than merely looking at instruments, is critical.